2022
DOI: 10.1177/20420188221102800
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin B12 levels and glycemic fluctuation in patients with type 2 diabetes mellitus

Abstract: Purpose: The aim of the study was to explore the correlation between serum vitamin B12 levels and glycemic fluctuation in patients with type 2 diabetes mellitus (T2DM). Methods: This study included 202 T2DM patients in whom blood glucose levels were recorded using a continuous glucose monitoring system retrospectively. Glycemic fluctuation was determined using the average daily risk range (ADRR), a diabetes-specific measure of the risk for hyper- and hypoglycemia. Results: Serum vitamin B12 levels were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to this study, serum vitamin B12 level was found not to be associated with blood glucose and HbA1c. A recent study has found that vitamin B12 replacement could improve glycemic control and blood glucose fluctuations (18). However, another study demonstrated that hyperglycemia alters vitamin B12 usage in the body and thus increases serum B12 levels (19).…”
Section: Resultsmentioning
confidence: 99%
“…According to this study, serum vitamin B12 level was found not to be associated with blood glucose and HbA1c. A recent study has found that vitamin B12 replacement could improve glycemic control and blood glucose fluctuations (18). However, another study demonstrated that hyperglycemia alters vitamin B12 usage in the body and thus increases serum B12 levels (19).…”
Section: Resultsmentioning
confidence: 99%